PENYALURAN ZAKAT FITRAH OLEH AMIL DI LUAR MUSTAHIQ DI MASJID AL-MANAR DESA TEMPAPAN KUALA - NIM. A1011211069, WAHIDAH (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Zakat is a form of worship prescribed in Islam and obligatory for every able Muslim. Zakat has a very important function, namely helping those in need and realizing social justice in society. One type of zakat is zakat fitrah which must be paid every month of Ramadan and must be distributed to eight groups of mustahiq as regulated in the Qur'an, Surah At-Taubah, verse 60 and Law Number 23 of 2011 concerning Zakat Management. However, in practice, the distribution of zakat fitrah carried out by amil at the Al-Manar mosque in Tempapan Kuala village has not been in accordance with these provisions, because in addition to zakat fitrah being distributed to the poor, needy, amil, and converts, zakat fitrah is also distributed to parties such as village shamans, midwives, gravediggers, Quran teachers, muezzins, ma'asyiral, preachers, and mosque imams. The research problem is formulated as follows: